Repositório arquivístico digital confiável para o patrimônio documental oriundo do processo judicial eletrônico - Rodrigues, Mateus de Moura (2015)
This paper presents an approach on the preservation of digital archival documents the activity of legal advice institutions, in other words, digital dossiers for electronic court proceedings. About this documentation, it is clear that it is part of the potential Documentary Heritage of these companies, demanding the adoption of conservation activities that provide the preservation and access of documents produced in this context. Therefore, this research aims to formalize recommendations for implementing a convenient digital environment in order to ensure the preservation of these documents and the maintenance of their authenticity. Permeate this purpose their identification as digital archival documents, the research about the adoption of document management practices in these institutions, the identification of the best Archival Digital Repository Digital to cater these companies and the development of recommendations for the implementation and use of it.As theoretical basis were approached Cultural Heritage and Documentary Heritage,Archivology and the archival document as their object of study, the archival management of digital documents and Digital Preservation. This research is classified as applied, qualitative and exploratory purposes, having a theoretical basis and is a case study. The data collection instruments were the bibliographic records and systematic observation to visualize the document management interventions in the legal advisory companies. As results, the research defined that digital documents produced in legal proceedings as archival documents, also a diagnosis based on systematic observation in law firms to illustrate the reality of them about the adoption of records management and the instruments used to Documentary Heritage definition. Was also analysed the attributes and features of the Archival Digital Repositories Archivematica and RODA in accordance with the OAIS model and the indication of Archivematica as the best suited repository to the research domain.Finally, the implementation and use recommendations for the Archivematica were prepared, passing to the preservation planning, ingest, archival storage, file formats normalization and the interoperability possibilities with archival description software to the digital Documentary Heritage dissemination. As conclusions, we could give as consolidated the main objective of the research, and the Archivematica proved to be able to comply with the demands of a digital environment capable to provide the preservation and the maintenance of the authenticity of archival documents digital stored, in accordance with the international reference standards. Key-words: Digital Preservation. Archival Digital Repository. Archival Digital Document. Archivology. Electronic Judicial Procedure. Documental Heritage